Peningkatan dan aktivitas enzim asetilkolinesterase pada nyamuk Aedes aegypti yang diseleksi dengan malation - Dwi Jayanti Gunandini; P. B. Wicaksana (Perhimpunan Entomologi Indonesia, 2005)
The Elevated and Activity of Acetilcholinesterase Enzyme on Aedes aegypti Selected by Malathion. The aim of this research was to study the effect of selection by malathion on the activity level Acetilcholinesterase enzyme on Aedes aegypti mosquitoes. Selection of Aedes aegypti larval by mean of malathion have been conducted for 20 generations. During the selection process time has been increased of concentration applied and exposure. For generation 0-5 (F0-F5), a concentration of 25 µl/l (24 ppm) was used to expose the larvae to malathion for five minutes. In generation 6-10 (F6-F10) the concentration has increased to 50 µl/l (48 ppm); in F11-F15 the concentration used was 100 µl/l (96 ppm) whereas in F16-F20 200µl/l (192 ppm) was used. Mosquito generations that would be regarded as representative and reference groups were F0, F5, F10, F15 and F20. The LC50 of F0, F5, F10, F15 and F20 was 0,025; 0,032; 0,042; 0,062 and 0,071 ppm respectively. Increases LT50 values was also observed in Aedes aegypti selected by malathion. The LT50 of F0, F5, F10, F15 and F20 generations was 7,9; 11,3; 18; 30,6 and 33,1 minutes respectively. The low levels of malathion resistance could be conferred by the elevated of α-esterase. The values of the α-esterase in F0, F5, F10, F15 and F20 were 0,155; 0,174; 0,203; 0,209 and 0,215 µmol/min/mg protein respectively. The acetilcholinesterase activities were also raised in F0, F5, F10, F15 and F20, the value of acetilcholinesterase activities were 20,35; 20,26; 23,14; 23,18 and 24,9%.